2009
DOI: 10.1159/000255973
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Associated with Atrial Fibrillation – Incidence and Early Outcomes in the North Dublin Population Stroke Study

Abstract: Background: Prospective population-based studies are important to accurately determine the incidence and characteristics of stroke associated with atrial fibrillation (AF), while avoiding selection bias which may complicate hospital-based studies. Methods: We investigated AF-associated stroke within the North Dublin Population Stroke Study, a prospective cohort study of stroke/transient ischaemic attack in 294,592 individuals, according to recommended criteria for rigorous stroke epidemiological studies. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
148
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 52 publications
15
148
1
12
Order By: Relevance
“…These findings are similar to those reported in Adelaide (23%) 3 , Rochester (30.3%) 27 and Iquique (28%) 28 . In contrast, the Dublin study reported 23.1% for AF-related stroke and 12.1% for non-AF-related stroke 23 .…”
mentioning
confidence: 79%
“…These findings are similar to those reported in Adelaide (23%) 3 , Rochester (30.3%) 27 and Iquique (28%) 28 . In contrast, the Dublin study reported 23.1% for AF-related stroke and 12.1% for non-AF-related stroke 23 .…”
mentioning
confidence: 79%
“…The majority of subtyped first-ever strokes were ischemic (84% [95% CI, 78-88]). Intracerebral hemorrhage comprised 11% (8)(9)(10)(11)(12)(13)(14)(15)(16), SAH 3% (1-6), and 3% (1-6) were undetermined.…”
Section: Stroke Subtypesmentioning
confidence: 99%
“…15 In the Dublin Stroke study, the presence of AF in association with a stroke, regardless of the cause, was reported in 31% of cases. 16 Applying the TOAST criteria to the Dublin study, 22% of all ischemic strokes were reported as cardioembolic from any cause. 11 In the Perth community stroke study of 1989, 15% of strokes were attributed to embolic infarction after review.…”
Section: Burden Of Cardioembolic Strokementioning
confidence: 99%
“…2 As embolias relacionadas com a FA são responsáveis por 15% dos acidentes vasculares cerebrais (AVC) 11 , que têm maior gravidade e pior prognóstico. 12 A incidência de AVC na FA não reumática é de cerca de 5% ao ano (quatro a cinco vezes maior que a da população em geral para qualquer grupo etário), 11,13 aumentando para 13 a 14% na FA com valvulopatia concomitante.…”
unclassified